Masalah Makan pada Anak : Definisi Hingga Penatalaksanaan - Abi Fauzan Pulungan; Dika Amalia (Vitalitas Medis : Jurnal Kesehatan dan Kedokteran, 2025)
Eating problems in children refer to various behaviors or conditions that interfere with a child's ability to consume food properly. This can include refusal of certain foods, difficulty chewing or swallowing, and unhealthy eating habits. Eating problems in children are not a focus in everyday life, so they become an ignored problem. The presence of eating problems in children has an impact on nutritional status and health in the future. Even eating behaviors that have been patterned since childhood can continue into adolescence and even adulthood. Parental eating habits and strategies used in feeding are dominant determinants of children's eating behavior and food choices. Therefore, examining eating problems in children is important to do because this problem can affect the growth and development of children if not handled properly so that fast and appropriate treatment is needed.